Conceptual model of reverse logistics management of health resorts - Serhii Voitovych; Liubov Lipych (Економічний форум)
In this scientific article, a conceptual model of reverse logistics management of sanatorium-resort institutions is formed, which meets the principles of implementing the concept of this type of management and provides efficiency conditions. The main purpose of the study is to form an actual and effective conceptual model of reverse logistics management of sanatorium-resort institutions in order to improve the management processes of such institutions and the processes of meeting the needs of consumers in these services. A monographic study of literature sources showed the absence of such an effective logistics management system in the management of sanatorium-resort institutions, which is expressed by the low capacity of institutions to meet the needs of consumers in sanatorium-resort treatment. The relevance of solving this scientific problem lies in the fact that the formed conceptual model of reverse logistics management of sanatorium-resort institutions will allow them to ensure the effectiveness of management itself and the efficiency of market functioning. The proposed conceptual model of reverse logistics management of health resorts contains factors, information and resources that form the entrance to the operating system; blocks of implementation, evaluation and transformation for reverse logistics management, which fill the operating management system; a list of effects of the implementation of reverse logistics management, which form the exit from the operating system. The methodological tools of the research were following: a systematic approach, logical and structural synthesis, methods of management analysis of logistics management processes, methods of logical generalization, and others. The object of the research was the reverse logistics management of sanatorium-resort institutions, and the subject was its conceptual model. The study demonstrates the methodological and applied content and logically justifies the completeness and effectiveness of the formed conceptual model of reverse logistics management of sanatorium-resort institutions. The results of the study can be useful for managers and managers of health resort services institutions to ensure the effectiveness of management processes for such service institutions